Second Order Confirmatory Factor Analysis of an Innovative Work Behavior for First-line Nurse Managers in Private Hospitals - Singchangchai, Phechnoy; Tantapong, Usa; Hakom, Nujaree; Patiganmonthon, Namfon; Kamolsirianan, Pattanan (Journal of Vongchavalitkul university, 2021)
Objectives: To analyze and to test construct validity using second order confirmatory factor analysis of innovative work behavior of first-line nurse managers in private hospitals Method: A descriptive research with a sample group of 200 first-line nurse managers in private hospitals recruited through stratified sampling. The research instrument was a five-point rating scale questionnaire on innovative work behavior with content validity index of 0.80 and Cronbach’s alpha coefficient of 0.85. Descriptive statistics, first order confirmatory factor analysis and second order confirmatory factor analysis were conducted. Results: When tested with second order confirmatory factor analysis, it was found that the construct validity of innovative work behavior of first-line nurse managers in private hospitals corresponded to the empirical data and the statistical values showed significant congruence with the criteria (c2 2nd order=42.04, df=61, p-value=0.96, RMSEA=0.00, GFI=0.92, AGFI=0.92, CFI= 1.00, NFI=0.95, RMR=0.015). There were 4 factors and 13 indicators with factor loadings that met the criteria (λ=0.63-0.75) consisting of innovative idea- exploration behavior (3 indicators), innovative idea-generation behavior (3 indicators), innovative Idea -championing behavior (4 indicators), and innovative idea-implementing behavior (3 indicators). The research results indicate that administrators should have a reliable measuring tool with valid construct for assessment or measurement of innovative work behavior of first-line nurse managers. This is to assess potential of people management to encourage them to have innovative work behavior or to create new things using talent management that would results in more innovations in nursing organizations.